Examining Scottish Enterprise's framework for action in life sciences. (20th November 2008) - Rosiello, Alessandro
This paper describes Scottish Enterprise (SE) 'Framework for Action' in life sciences and examines its effectiveness through the lenses of cluster theory and selected concepts from the literature on market and systemic failure. The focus is on the framework's capability to improve the competitive performances of biotechnology firms and strengthen networks. The empirical study gathers the views of the managers and technical directors of 18 Scottish biotechnology companies and provides insights as regards firms' locational choices, collaborative and commercial strategy and the materialisation of a local socio-institutional infrastructure. Easy access to finance, infrastructure, Intellectual Property (IP) and skilled people remain crucial for the achievement of strategic goals. Simultaneously, local and distant networks are beginning to emerge and to have a positive impact on firms' capability to expand research and, to a lesser extent, reach global markets. Scottish companies seem to benefit from mechanisms that reduce cognitive distance locally and the impact of geographical distance from foreign partners.